Determining the factors that promote higher order thinking skills in mathematics technology enhanced learning environment: perspective from university students - Letchumanan, M.; Husain, S. K. S.; Ayub, A. F. M.; Kamaruddin, R.; Zulkifli, N. N. (Institute for Mathematical Research, Universiti Putra Malaysia, 2023)
The purpose of this study was to investigate the factors that influence promotion of higher order thinking skills (HOTS) among mathematics higher learning institution students in technology enhanced learning environment (TEL) in Malaysia. The study used descriptive research design. Data of the study was collected by using quantitative research approach. A total of 250 students from three public universities participated in the study. The study explores the relationship between students' attitude towards technology use and organisation support towards promotion of HOTS in mathematics TEL environment. Results from structural equation modelling reported that students' attitude towards technology use had a positive direct relationship with HOTS. Meanwhile, organisation support had a positive direct relationship with students' attitude towards technology use which in turn indirectly influence promotion of HOTS. The hypothesized structural equation model accounted for 20.2% of the variance in HOTS. The results indicated a need for further studies in order to examine factors that predict promotion of HOTS in mathematics TEL at higher learning institutions in Malaysia.